Pathway and interaction analysis of IMCHA Model: An initiative of implementation research in Uganda and South Sudan - Musoke, Jenipher T.; Mugirwa, Patrick; Nakimuli, Eva (African Journal of Reproductive Health, 2024)
This article was published in The African Journal of Reproductive Health [©2021 Rights managed by AJRH] and the definite version is available at: https://doi.org/10.29063/ajrh2021/v25i3s.6 The Article's website is at: https://www.ajrh.info/index.php/ajrh/article/view/2801